Quantitative analysis of somatically acquired and constitutive uniparental disomy in gastrointestinal cancers. Issue 3 (3rd December 2018) - Torabi, Keyvan; Erola, Pau; Alvarez‐Mora, Maria Isabel; Díaz‐Gay, Marcos; Ferrer, Queralt; Castells, Antoni; Castellví‐Bel, Sergi; Milà, Montserrat; Lozano, Juan José; Miró, Rosa; Ried, Thomas; Ponsa, Immaculada; et al.
Abstract : Somatically acquired uniparental disomies (aUPDs) are frequent events in solid tumors and have been associated with cancer‐related genes. Studies assessing their functional consequences across several cancer types are therefore necessary. Here, we aimed at integrating aUPD profiles with the mutational status of cancer‐related genes in a tumor‐type specific manner. Using TCGA datasets for 1, 032 gastrointestinal cancers, including colon (COAD), rectum (READ), stomach (STAD), esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), we show a non‐random distribution of aUPD, suggesting the existence of a cancer‐specific landscape of aUPD events. Our analysis indicates that aUPD acts as a "second hit" in Knudson's model in order to achieve biallelic inactivation of tumor suppressor genes. In particular, APC, ARID1A and NOTCH1 were recurrently inactivated by the presence of homozygous mutation as a consequence of aUPD in COAD and READ, STAD and ESCC, respectively. Furthermore, while TP53 showed inactivation caused by aUPD at chromosome arm 17p across all tumor types, copy number losses at this genomic position were also frequent. By experimental and computationally inferring genome ploidy, we demonstrate that an increased number of aUPD events, both affecting the whole chromosome or segments of it, were present in highly aneuploid genomes compared to near‐diploid tumors. Finally, the presence of mosaic UPD was detected at a higher frequency in DNA extracted from peripheral blood lymphocytes of patients with colorectal cancer compared to healthy individuals. In summary, our study defines specific profiles of aUPD in gastrointestinal cancers and provides unequivocal evidence of their relevance in cancer. Abstract : What's new? Somatically acquired uniparental disomies (aUPDs), in which two copies of a chromosome originate from the same parent, have been documented in various human cancers. Here, the authors examined the frequency of aUPDs in different gastrointestinal cancer types. Events involving aUPDs were found to occur at high incidence in gastrointestinal cancers and at increased frequency particularly in highly aneuploid genomes. The data also reveal a nonrandom distribution of aUPDs, with evidence of biallelic inactivation of tumor suppressor genes and activation of oncogenes in a tumor type‐specific manner. The findings suggest that aUPDs are functionally relevant in gastrointestinal malignancies.